Transcription of DWARF4 Plays a Crucial Role in Auxin-Regulated Root Elongation in Addition to Brassinosteroid Homeostasis in Arabidopsis thaliana - Yoshimitsu, Yuya (Public Library of Science, 2011)

(untitled)
The expression of DWARF4 (DWF4), which encodes a C-22 hydroxylase, is crucial for brassinosteroid (BR) biosynthesis and for the feedback control of endogenous BR levels. To advance our knowledge of BRs, we examined the effects of different plant hormones on DWF4 transcription in Arabidopsis thaliana. Semi-quantitative reverse-transcriptase PCR showed that the amount of the DWF4 mRNA precursor either decreased or increased, similarly with its mature form, in response to an exogenously applied bioactive BR, brassinolide (BL), and a BR biosynthesis inhibitor, brassinazole (Brz), respectively. The response to these chemicals in the levels of β-glucuronidase (GUS) mRNA and its enzymatic activity is similar to the response of native DWF4 mRNA in DWF4::GUS plants. Contrary to the effects of BL, exogenous auxin induced GUS activity, but this enhancement was suppressed by anti-auxins, such as α-(phenylethyl-2-one)-IAA and α-tert-butoxycarbonylaminohexyl-IAA, suggesting the involvement of SCF(TIR1)-mediated auxin signaling in auxin-induced DWF4 transcription. Auxin-enhanced GUS activity was observed exclusively in roots; it was the most prominent in the elongation zones of both primary and lateral roots. Furthermore, auxin-induced lateral root elongation was suppressed by both Brz application and the dwf4 mutation, and this suppression was rescued by BL, suggesting that BRs act positively on root elongation under the control of auxin. Altogether, our results indicate that DWF4 transcription plays a novel role in the BR-auxin crosstalk associated with root elongation, in addition to its role in BR homeostasis.